EFFECTIVE TEACHING METHODS IN TEACHING ENGLISH (Intent Research Scientific Journal, 2023)
Due to the wide spread and use of English language throughout the globe, teaching and learning English language has got really surprising importance. This has raised a number of questions related to effective English language teaching. In this scenario, with the help of author’s own experience in teaching English language for more than a decade, this article elaborates different factors that are responsible for effective English language teaching. Teacher, methods and techniques, teaching materials and learner themselves are such factors that are responsible for effective English language teaching.